Breaking Language Barriers: Centre For Modern Languages Universiti Malaysia Pahang Al Sultan Abdullah Excels At HE ELCA 2023 - Ezihaslinda, Ngah; Amy Zulaikha, Mohd Ali; Rosnani, Ismail (2023)
7 December 2023, Tanjung Malim - The Centre for Modern Languages (CML) at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has distinguished itself by organising the participation of thirty-two students in various online competitions at the Higher Education English Language Carnival (HE ELCA) 2023.